2014
DOI: 10.1080/14330237.2014.980626
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress of professional nurses in South Africa

Abstract: The objective of this study was to identify occupational stressors for professional nurses in South Africa. A cross-sectional survey design was used. A stratified random sample of professional nurses (n = 818; females = 97%) in hospitals in South Africa was used. The Nursing Stress Indicator (NSI) was administrated together with a biographical questionnaire. Three internally consistent stress factors, namely lack of organisational support, job demands and nursing-specific demands, were extracted. The most seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 52 publications
1
14
0
7
Order By: Relevance
“…This is the first cross-sectional study on emotional well-being and work engagement of nurses who moonlight in private hospitals in South Africa. Although there is an abundance of research on emotional well-being of nurses (Van der Colff & Rothmann, 2014;Khamisa et al, 2015;Khunou, & Davhana-Maselesele, M., 2016;Makhado & Davhana-Maselesele, 2016;Mashego et al, 2016;Dlamini & Visser, 2017;Roomaney, Steenkamp, & Kagee, 2017;Wentzel & Brysiewicz, 2018) in South Africa, there are no studies specifically focusing on emotional well-being of nurses who moonlight. We defined well-being by investigating levels of general health, mental health, emotional exhaustion, personal accomplishment, compassion satisfaction and compassion fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is the first cross-sectional study on emotional well-being and work engagement of nurses who moonlight in private hospitals in South Africa. Although there is an abundance of research on emotional well-being of nurses (Van der Colff & Rothmann, 2014;Khamisa et al, 2015;Khunou, & Davhana-Maselesele, M., 2016;Makhado & Davhana-Maselesele, 2016;Mashego et al, 2016;Dlamini & Visser, 2017;Roomaney, Steenkamp, & Kagee, 2017;Wentzel & Brysiewicz, 2018) in South Africa, there are no studies specifically focusing on emotional well-being of nurses who moonlight. We defined well-being by investigating levels of general health, mental health, emotional exhaustion, personal accomplishment, compassion satisfaction and compassion fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…African studies, which reported higher levels of emotional exhaustion among nurses (Makhado & Davhana-Maselesele, 2016;Van der Colff & Rothmann, 2014). More specifically high levels of emotional exhaustion were found: (a) among 34.6% of registered nurses in the private, public, hospital, community, psychiatric and management sectors of seven provinces of South Africa (Van der Colff & Rothmann, 2014) and (b) among 53% of nurses caring for people living with HIV/AIDS at a regional hospital (Makhado & Davhana-Maselesele, 2016). Given the low scores on emotional exhaustion (ie, low risk for burnout), we…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotion-focused coping aims to reduce the intensity of emotions caused by a stressful situation, whereby problem-focused coping attempts to change the problematic situation itself. Although there is evidence that nurses frequently utilise emotion-focused coping strategies to manage work-related stress [50], the implications for wellbeing are mixed and negative, and positive effects on mental health have been reported [51,52,53,54]. …”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that emotional expression can help people process their emotional reactions, facilitate emotional adjustment, and enhance mental health and life satisfaction [57,58]. There is also evidence that nurses who use emotional expressive coping styles are at lower risk of emotional exhaustion [54]. Emotional venting may help nurses manage the emotional demands of their work for several reasons.…”
Section: Introductionmentioning
confidence: 99%